Spatio-Temporal Changes in Patterns of Land Use and Land Cover in Peri - Urban Areas of Faisalabad City - Afzal, Iqra; Waseem, Liaqate Ali; Khurshid, Madiha; Maqbool, Muhammad Shahid (Pakistan Journal of Humanities and Social Sciences, 2023)
The changes in land use occurs with the passage of time in an area where the priorities of living standard changes. The increase in population and better socio-economic opportunities within urban localities influences the peripheral areas as well as the proximities. The aims of the study changes in land use patterns in peri urban areas. The current research evaluated the variation in land use preferences in Faisalabad city during the 2000, 2010 and 2017, covering 18 years. The change is detected through satellite images by applying the supervised classification in specified classes including vegetation, built up areas, barren land and water bodies. The analyses of the acquired images disclosed that the dominant land utilization in the peri-urban zone is the built-up or infrastructure development. This urban expansion and development mostly influenced the agricultural land or vegetation cover, as results vegetation cover reduced rapidly. Out of the total land area, the urban infrastructure area with 24% in 2000, increased to 46% in 2017. The results further indicated that the city is expanding rapidly towards the peri-urban areas. For the most part of the peri-urban, land is converted to urban land uses as for housing, infrastructure and commercial activities.